Johnny Guitar [videorecording (DVD)] - Crawford, Joan, 1908-1977; Hayden, Sterling, 1916-1986; McCambridge, Mercedes; Bond, Ward, 1903-1960; Borgnine, Ernest, 1917-2012; Chanslor, Roy, 1899-1964 (Olive Films ; Paramount Home Entertainment, 2012)
Saloon owner Vienna battles the local townspeople headed by Emma, the local sexually repressed, lynch-happy female rancher out to frame her for a string of robberies. Johnny Logan is a guitar-strumming drifter with a dark past who was once in love with Vienna and has been offered a job in her saloon. Nicholas Ray's epic western is considered one of the most original westerns of all time. The women are far tougher than the men and some saw a bizarre allegory for the McCarthy era Red Scare.